Stories from the Trenches: Exploring Strategies Used by a Group of African American Female Teachers to Enhance the Learning Experiences of Black Students - Reeves, Lawonda (My University, 2021)
In an effort to learn how to best educate Black students from low socioeconomic schools who were struggling academically and performing significantly lower than their White counterparts, this study unpacked the educational and professional experiences of the researcher and five like participants and reflected upon those experiences as a critical race theorist researcher. To further understand effective strategies used by other teachers, the theoretical framework of critical race theory (CRT) was used to explore the experiences of five African American female teachers who had success educating underachieving Black students. Interviews were conducted with each of the five women and group discussions were held with the same interviewees to gather additional data. Subsequent narrative data were used to construct three prominent themes. The themes were centered on building relationships with students and their families, creating high expectations for students to meet or exceed, and implementing cultural connections in the classroom to enhance academic success. This study contributes to the growing body of literature on addressing the opportunity gap to combat the educational disparities in education for students of color. The results suggest teachers can help resolve the opportunity gap conundrum if they are willing to meet students where they are. Results also suggest the need for researchers to do more qualitative research on teachers’ strategies to help educate academically low achieving Black students through the implementation of culturally relevant pedagogy. Keywords: African American Female Teachers, Enhance the Learning Experiences of Black Students, Exploring Strategies
ACKNOWLEDGEMENTS vi -- CHAPTER 1 INTRODUCTION 1 -- Background 4 -- Researcher as Instrument 7 -- Educational Recollections 8 -- Professional Recollections 12 -- Statement of Problem 16 -- Goals and Purposes 24 -- Research Questions 26 -- Summary 27 -- CHAPTER 2 CONCEPTUAL FRAMEWORK 28 -- The Model and Its Relevance 28 -- Selected Literature 29 -- School Resources and Teacher Expectations 31 -- Culturally Relevant Teaching and Negative Stereotyping 34 -- Promising Practices and Strategies 37 -- Critical Race Theory 40 -- Summary 49 -- CHAPTER 3 METHODS 50 -- Research Design 52 -- Participants 55 -- Data Collection 58 -- Data Analysis 61 -- Validity 65 -- Summary 68 -- CHAPTER 4 STORIES: MINE, STUDENTS’, AND THOSE -- FROM THE SHE-DECK 69 -- Personal Plights 71 -- Students Who Stick In My Head 75 -- Introducing Sassy 76 -- Introducing Cloud 79 -- Introducing Runner 82 -- Introducing MJ 83 -- Introducing Preacher 85 -- Introducing Marta Bus 87 -- Introducing Bring It 89 -- Introducing Caregiver 90 -- Introducing Ain’t Got Time 91 -- Strategies That Worked For These Kids 93 -- Training Day 94 -- Extrinsic Rewards 95 -- Change in Perspective 96 -- The Blueprint 97 -- Dialogue Discussions 100 -- Mrs. Lou Parish 102 -- Mrs. Urban Scholar 111 -- Mrs. Talented Tenth 121 -- Mrs. Liberty City 127 -- Mrs. Prioress High 132 -- Common Factors 139 -- She-Deck Sessions 140 -- Black Teacher Magic (BTM) and Critical Race Theory 141 -- Black Teacher Magic and Culturally Relevant Pedagogy 156 -- Black Teacher Magic and Deficit Thinking 165 -- Black Teacher Magic, Traditional and Non-Traditional Strategies 171 -- Summary 180 -- CHAPTER 5 CONCLUSIONS 181 -- Relationships Matter 186 -- TeacherExpectations Matter 187 -- BlackCulture Matters 189 -- Limitations of the Study 190 -- Recommendations to Guide Further Research 191 -- REFERENCES 194 -- APPENDIX A IRB APPROVAL 215 -- APPENDIX B EMAIL INVITATION TO PARTICIPANTS 217 -- APPENDIX C INFORMED CONSENT SCRIPT 220 -- APPENDIX D TEACHER PARTICIPANT INTERVIEW QUE
Keywords: African American students; African American women teachers; Critical race theory; Dissertations, Academic--United States; Learning strategies